The specter of Babel a reconstruction of political judgment - Thompson, Michael J. 1973- (State University of New York Press, 2020)
"Boldly presents a new way of thinking about perennial political concepts such as freedom, justice, and the common good"--
Keywords: Politische Philosophie; Critical theory; Social sciences / Philosophy; Ontology; Political sociology